Number of Osteoblasts and Osteoclasts in Combination Carbonate Hydroxyapatite, Platelet Rich Fibrin (PRF) and Antioxidant in Socket Rats Wistar After Tooth Extraction - Widarena, Rachma; Marlie, Hengky; Rubianto, M.; Setiawatie, Ernie Maduratna (Indonesian Journal of Dental Medicine, 2021)
Background: Bone graft materials have been used extensively to support bone healing after tooth extraction. Bone healing could be increased reactive oxygen species (ROS) that prolong the phase of the inflammatory and delay reparative phase. Antioxidants are substances that can improve and reduce the number and the damage produced by ROS. Hence, the utilization of antioxidant which is utilized in conjunction to Carbonate hydroxyapatite is expected to increase the success of bone healing. Purpose: The aim of this study is to compare the number of osteoblasts and osteoclast in the process of bone healing after employing Carbonate Hydroxyapatite and antioxidant in the Wistar rats' incisor tooth extraction socket. Methods: Twenty-seven male Rattus norvegicus strain Wistar rats were divided into 3 treatment groups. This study uses a post-test only control design. Sample of 27 rats were divided into 3 groups. Mandibular incisive is extraction. Group 1, socket is lefted to fill with blood (control). Group 2, socket is filled bonegraft and antioxidants and group III, socket is filled antioxidants, bonegraft and platelet rich fibrin (PRF). After that, the wound is sutured. On day 14, the mice are terminated then viewed in microscopy of osteoblasts. The preparation of the bone tissues was given the staining by hematoxylin-eosin and then the numbers of the osteoblasts and osteoclast were calculated. Results: Statistical testing by using one-way ANOVA has proved that there are significant differences in the number of osteoblasts in all 3 groups (p = 0.000). The highest numbers of osteoblasts were found in the group that was given Carbonate Hydroxyapatite combined with antioxidant and PRF and the lowest numbers of osteoblasts were found in the control group. Conclusion: Combination bonegraft, antioxidants and PRF could be increased the highest number of osteoblasts and could be decreased the lowest number of osteoclasts compared with control group and the group bonegraft and antioxidants.